North and south / L. R. Lewis. - Lewis, Leo Rich, 1865-1945, composer. (Tufts University. Tisch Library., 2019)
Tufts College, Massachusetts : Tufts College Bookstore, 1918.; 1 online resource (1 score (23 parts)); For full military band.; Includes parts for oboe, coronet in B♭, horn in E♭, baritone horn, trombone, tenor horn in B♭, tuba, drums, poccolo in D♭, flute in C, clarinet in B♭, clarinet in E♭, alto saxophone in E♭, tenor saxophone in B♭, and bassoon.